Empowering women to be more physically active through high-intensity resistance training - Streetman, Aspen Elaine (Kansas State University, 2024)
Background: Empowering women is a global sustainable development goal. Being empowered means being able to accomplish goals despite adversity. Women are less likely than men to meet the physical activity guidelines, perhaps because they do not feel empowered. Feeling empowered by exercise may increase exercise adherence. Engaging in regular physical activity offers benefits for the body and the mind. Powerbuilding is a popular form of resistance training combining powerlifting with body building exercises that, to our knowledge, has not been used as an exercise intervention. The purpose of this dissertation is four-fold: 1) examine how empowerment is defined and measured, especially as it relates to physical activity; 2) determine if some types of physical activity are ranked more empowering than others; 3) explore the relationship between self-rated empowering exercise types, exercise engagement, and exercise self-efficacy; and 4) examine the effects of an applied powerbuilding intervention on physical activity, strength, and empowerment. Methods: This dissertation comprises three studies (Chapters 2, 3, and 4). The first, a narrative review complying with the Scale for the Assessment of Narrative Review Articles guidelines, explored sports participation as a mechanism to facilitate empowerment globally. The second study implemented an explanatory sequential mixed-methods design (survey N = 147; interviews N = 17). It examined the relationship between physical activity empowerment, engagement, and exercise self-efficacy. The third study (N = 18) in this dissertation was an applied exercise intervention that investigated the impact of an eight-week powerbuilding intervention on women’s physical activity, strength, and empowerment. Results: Chapter 2 found empowerment is inconsistently defined and measured between geographical contexts, yet sports empowerment defies geography. Sports empowerment describes feelings of empowerment that are the product of sports experiences that spillover to daily life. Results in Chapter 3 found that women ranked resistance training as the most empowering form of physical activity in which they participated. However, physical activity engagement and self-efficacy for exercise did not vary statistically among women who were empowered by resistance training compared to those who were empowered by other types of physical activity. Four themes emerged from interview data. They were: 1) women’s physical activity participation barriers are gender-centric, 2) physical activity participation benefits extend beyond physical health, 3) some exercise types are more empowering than others, and 4) empowerment and enjoyment are closely related. Results in Chapter 4 found that an eight-week powerbuilding intervention elicited significant changes in physical activity where participants' total physical activity increased ([t(17) = 3.52, p = 0.003, d = 0.83]), as did the participants who met the physical activity guidelines (Z = -3.32, p = 0.001) from pre- to post-intervention. Strength increased significantly from pre- to post-intervention in the squat (Z = -3.73, p < 0.001), bench press (Z = -3.73, p < 0.001), and deadlift [t(17) = 16.41, p < 0.001; d = 3.87]. High exercise empowerment (56.3 ± 6.6; out of 65 points) resulted from the intervention; empowerment in exercise scores ranged from 40 to 65, and six were over 60. Conclusion: Measuring empowerment in physical activity and exercise remains challenging, but some types of physical activity and exercise are more empowering than others. Feeling accomplished after a demanding workout facilitates feelings of empowerment. Exploring empowerment in exercise may reveal mechanisms to facilitate exercise self-efficacy and engagement in physical activity. Powerbuilding is inherently empowering for individuals with no powerbuilding experience. Lifting heavy weights and building muscle mass was empowering and increased engagement in physical activity. It is critical to encourage women to participate in empowering physical activity to enhance their physical, mental, and social health.
Keywords: Empowerment theory; Women's health; Powerbuilding; Exercise; Muscle-strengthening guidelines